Book Reviews (The ecumenical review, 1952)
Book reviewed in this article: EVANGELISM — THE RAISON D'ÊTRE OF THE CHURCH: Revelation and Evangelism, by F. W. Dillistone. EVANGELISM — THE RAISON D'ÊTRE OF THE CHURCH: Predikan, En Principiell Studie, by G. Wingren. EVANGELISM — THE RAISON D'ÊTRE OF THE CHURCH: Grundriss der praktischen Theologie, by A. D. Müller. EVANGELISM — THE RAISON D'ÊTRE OF THE CHURCH: The Theology of Evangelism, The Gospel in the World of Today, by H. Cook. EVANGELISM — THE RAISON D'ÊTRE OF THE CHURCH: The Practice of Evangelism, by B. Green. EVANGELISM — THE RAISON D'ÊTRE OF THE CHURCH: Evangelische Benadering van de Mens. EVANGELISM — THE RAISON D'ÊTRE OF THE CHURCH: The Divine Charge to the Christian in the Church, by J. C. G. Kotze. EVANGELISM — THE RAISON D'ÊTRE OF THE CHURCH: The Household of Faith, An Essay on the Changing Pattern of the Church's Life, by R. T. Morton. EVANGELISM — THE RAISON D'ÊTRE OF THE CHURCH: L'esprit missionnaire, by G. H. Michonneau et H. Ch. Chery. EVANGELISM — THE RAISON D'ÊTRE OF THE CHURCH: Au Cœur des Masses, by R. Voillaume. WHAT THE CHURCHES OWE TO WOMEN: The Service and Status of Women in the Churches, by Kathleen Bliss. WHAT THE CHURCHES OWE TO WOMEN: A Study of the Man-Woman Relationship. LOVE FOR HERETICS: Vision and Action: The Problems of Ecumenism, by L. A. Zander. DISCOVERIES OF A PRISONER-OF-WAR IN RUSSIA: Und führen wohin du nicht willst, by Helmut Gollwitzer. A BOOK OF ORIGINS: Ecumenical Foundations. A History of the International Missionary Council and its nineteenth century background, by William Richey Hogg. EUROPEAN UNITY: The Western Political Tradition, by R. H. Tawney. EUROPEAN UNITY: The Roman Catholic Church and European Unity, by P. van Waeyenbergh. EUROPEAN UNITY: Europe and America — Their Contributions to the World Church, by Daniel Jenkins. EUROPEAN UNITY: Lettre aux députés européens, by Denis de Rougemont. EUROPEAN UNITY: L'Europe en jeu (l'Evolution du Monde et des Idées), by Denis de Rougemont. EUROPEAN UNITY: Le Problème de l'Union européenne, by Olivier Philip. EUROPEAN UNITY: Policy for the West, by Barbara Ward. EUROPEAN UNITY: Making Western Europe Defensible, by Th. Geiger and H. van B. Cleveland. CHRISTIAN ATTITUDES TO WAR AND PEACE: War is Contrary to the Will of God. CHRISTIAN ATTITUDES TO WAR AND PEACE: Steps to Peace. A Quaker view of U.S. Foreign Policy, prepared for the American Friends' Service Committee. CHRISTIAN ATTITUDES TO WAR AND PEACE: La Guerre et la Paix, by Karl Barth. CHRISTIAN ATTITUDES TO WAR AND PEACE: The Theological Basis of Christian Pacifism, by Charles E. Raven. CHRISTIAN ATTITUDES TO WAR AND PEACE: Christianity and the Reconciliation of the Nations, by C. H. Dodd. CHRISTIAN ATTITUDES TO WAR AND PEACE: World Religions and the Hope for Peace, by D. R. Williams. THE CHRISTIAN BASIS OF JUSTICE AND LAW: Law and the Laws, being the Marginal Comments of a Theologian, by Nathaniel Micklem. THE CHRISTIAN BASIS OF JUSTICE AND LAW: Natural Law, An Introduction to Legal Philosophy, by A. P. d'Entrèves. THE CHRISTIAN BASIS OF JUSTICE AND LAW: Man and State, by Eivind Berggrav. THE CHRISTIAN BASIS OF JUSTICE AND LAW: German edition: Der Staat und der Mensch. THE CHRISTIAN BASIS OF JUSTICE AND LAW: Le Fondement thèologique du Droit, by Jacques Ellul. Delachaux et Niestlé, Neuchâtel et Paris, 1946. 112 pp. Sw. fr. 4.25. German translation: Die theologische Begründung des Rechts. THE CHRISTIAN BASIS OF JUSTICE AND LAW: Rechtsgedanke und biblische Weisung, by Erik Wolf. (Forschungen der Evang. Akademie, Band 5.) THE CHRISTIAN BASIS OF JUSTICE AND LAW: Gerechtigkeit und Freiheit, by Ernst Wolf and Hans Emil Weber. THE CHRISTIAN BASIS OF JUSTICE AND LAW: Die Treysa-Konferenz über das Thema “Gerechtigkeit in biblischer Sicht,” THE CHRISTIAN BASIS OF JUSTICE AND LAW: Kirche und Recht. Ein vom Rat der evangelischen Kirche in Deutschland veranlasstes Gespräch über die christliche Begründung des Rechts. THE CHRISTIAN BASIS OF JUSTICE AND LAW: Guds och Sveriges Lag. Studier i den lutherska socialetikens historia, by Ruben Josefson. SOCIOLOGY AND RELIGION: Sociology and Religion, by Joachim Wach. SOCIOLOGY AND RELIGION: Aus den Schriften zur Religionssoziologie, by Max Weber. SOCIOLOGY AND RELIGION: Gesammelte Aufsätze zur Religionssoziologie, by Max Weber. SOCIOLOGY AND RELIGION: From Max Weber: Essays in Sociology. SOCIOLOGY AND RELIGION: Studien zur Religionssoziologie, by W. Trillhaas. SOCIOLOGY AND RELIGION: Lumen Vitae. Revue internationale de la Formation religieuse. SOCIOLOGY AND RELIGION: Godsdienst en Maatschappij, by W. H. Vermooten en W. de Fries. SOCIOLOGY AND RELIGION: Sociologie en Kerk. Een bundel studies met een inleiding van Dr. W. Banning. BARTH FROM A ROMAN CATHOLIC PERSPECTIVE: Karl Barth: Darstellung und Deutung seiner Theologie, by Hans Urs von Balthasar. AN EPISODE IN EAST-WEST RELATIONSHIP: Die abendländische Sendung der östlich-orthodoxen Kirche, by Ernst Benz. IMPRESSIONS OF GERMAN PROTESTANTISM: German Protestantism since Luther, by Andrew L. Drummond. FRENCH CATHOLICISM ON THE MOVE: A Church Renascent. A Study in modern French Catholicism, by D. Watmough.